The effectiveness of community participation in planning and urban developments : thesis presented in partial fulfilment of the requirements for the Masterate of Resource and Environmental Planning at Massey University - Van Empel, Christoffel (Massey University, 2007)
In recent years, community participation in planning and urban development processes has experienced an increased attention in planning process and public awareness of its importance in planning and public decision-making processes. There seems to be a growing expectation from the public to be involved, in order to hold the policymakers accountable. Contemporary planning theories acknowledge the value of community participation in the development processes of our built environment, suggesting that community involvement has the potential to achieve a more sustainable outcome. Research in this field suggests that citizen participation can generate trust, credibility, and commitment regarding the implementation of policies, and that the conflicts are resolved during the planning process rather than delaying implementation of completed plans. How and to what extent public involvement has an influence on the planning process however is dependent on the conditions such processes are operating. This thesis will investigate the tools available to measure the effectiveness of public participation and their influences on urban development and planning processes. The various approaches of community involvement will be studied to ascertain how the characteristics of public involvement affects the planning process, and to what extent the objectives of the parties involved are considered and reconciled in that process. This research will be based on a qualitative research strategy, by identifying and examining the characteristics of existing participation techniques in planning processes through a literature review. These findings will be used to develop a framework of indicators for the assessment of the effectiveness of community involvement in urban developments, by way of a case study. The case study used for this research is the "Greater Christchurch Urban Development Strategy', a collaborative initiative for the development of a growth strategy for the Christchurch region. The literature review has identified aspects such as, level, timing and extent of participation processes, type, quality and availability of technical information, and techniques employed, as process influencing characteristics for community involvement. While, with a focus on the participation process, indicators such as legitimacy, ideology, fairness, equal power, competence, social learning, efficacy, responsiveness, representativeness, capacity and willingness, have been suggested as tools to measure the effectiveness of community involvement. The 'effectiveness' indicators as extracted from the literature review have been found valuable for the assessment of the community participation process and have been used as a framework for the analysis of the process in the case study, by observing the communication and consultation process and conducting a questionnaire survey of key stakeholders in the project. The case study has learned that, although the use of the individual indicators has been beneficial for the analysis of the process, the identified indicators have the potential to influence each other, suggesting that they should not be evaluated independently. The findings of this research can be summarized as follows: • Most sectors of the community seem to have an interest in their built environment and associated urban planning processes, provided that their involvement is encouraged by stimulating information on the relevant issues and expertise is provided to support their contributions. • Although no conclusive outcomes with regard to the motivation of the various participants in the process have been reached, the professionals involved in the projcct seem to have a networking and sharing of expertise focused interest. • A strong commonality in the views from the public has been observed, with a focus on the 'big picture' rather than self-interests. • Collaborative planning has been experienced as an effective technique for consensus building between the professionals involved in the process. • The quality of resources and allocation of time seem to be influential elements for a community participation process. Although, due to the timeline of the case study, the research has been limited to the community participation process related indicators, the observation of the process has suggested that process and outcomes should not be separated and that further research to assess the influences of the community involvement on the product outcomes would be valuable.
Keywords: City planning; Community participation; Urban development; Public decision-making